1997
DOI: 10.1212/wnl.49.1.229
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of diabetic polyneuropathy using a composite score in the Rochester Diabetic Neuropathy Study cohort

Abstract: Because there are little satisfactory data on change in severity of diabetic polyneuropathy (DP) over time from study of population-based cohorts of diabetic patients in epidemiologic surveys of DP, it is difficult to predict outcome or morbidity or to identify risk factors; it is also difficult to estimate statistical power for use in controlled clinical trials. In this longitudinal study of almost 200 patients from the Rochester Diabetic Neuropathy Study (RDNS) cohort, we assess which symptoms, clinical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
294
0
12

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(310 citation statements)
references
References 13 publications
4
294
0
12
Order By: Relevance
“…The present follow-up studies provide new insights into the progression of muscle dysfunction in diabetes in relation to neuropathy. Nerve function declines with diabetes duration [22] leading to denervation and loss of muscle strength in patients with neuropathy [7]. In the present study we have shown that muscle volume in the lower leg was more than halved during an observational period of 13 years in type 1 diabetic patients with severe neuropathy and that in patients with a milder degree of neuropathy one fifth of the foot muscle volume was lost over a decade.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The present follow-up studies provide new insights into the progression of muscle dysfunction in diabetes in relation to neuropathy. Nerve function declines with diabetes duration [22] leading to denervation and loss of muscle strength in patients with neuropathy [7]. In the present study we have shown that muscle volume in the lower leg was more than halved during an observational period of 13 years in type 1 diabetic patients with severe neuropathy and that in patients with a milder degree of neuropathy one fifth of the foot muscle volume was lost over a decade.…”
Section: Discussionsupporting
confidence: 47%
“…Progressive deterioration of nerve conduction variables, autonomic tests, sensory detection thresholds and clinical examination scores can be slowed or prevented by tight glycaemic control [22,33,34]. To our knowledge, there is only one follow-up study on diabetic muscle mass and strength including older type 2 diabetic patients, but the participants were not characterised with respect to degree of neuropathy [27].…”
Section: Discussionmentioning
confidence: 99%
“…While not applied previously in ALS to our knowledge, ALS/SURV is similar to the CAFS and composite statistics used in studies where endpoints involved nerve conductions 23, 24. When there is high mortality, combining functional status with survival duration has greater comparative power and provides additional insight into potential efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation was approved by the Institutional Review Board of the University of Michigan Medical School, and participants were consented according to the Declaration of Helsinki. The criteria for inclusion within this study cohort were evidence of symptomatic clinical peripheral neuropathy based on the Michigan Neuropathy Symptom Instrument (MNSI), Michigan Diabetic Neuropathy Score (MDNS) [24][25][26] and an abnormality in at least one of the following: (1) nerve conduction studies (NCS) of the median motor and sensory responses, tibial and peroneal motor responses and sural sensory response on the left sides, (2) CASE IV quantitative sensory testing (QST) (≥95 th percentile compared to gender and age matched controls for cold detection threshold (CDT) in the dorsal foot or vibration detection threshold (VDT) at the great toe) [27,28] or (3) quantitative sudomotor axon reflex testing (QSART) sweat volume (≤5 th % at one of four sites: medial forearm 75% of the distance from the ulnar epicondyle to the pisiform bone, the proximal leg, medial distal leg, and proximal foot [29,30]. Participants also required glucose measurements consistent with either IGT or impaired fasting glucose (IFG) on at least two separate tests of IGT or IFG, using current definitions for these disorders of glucose regulation [31].…”
Section: Participantsmentioning
confidence: 99%